The Quality of Electronic Educational Resources Evaluation for the Postgraduate Education System - Kashyna, Ganna; Shuliak, Yuliia (Journal of Education, Technology and Computer Science, 2019)
The article is devoted to the methodology of evaluation of the quality of electronic educational resources. The model of integral assessment of their qualities which provides the assessment of each individual training module is developed. Important elements of the integral assessment of the qualities of the e-learning module on every procedural stage are the order and evaluation criteria. Such system of evaluation contains parameterswhich characterize the innovative, technological and semantic qualities of the educational module. Such system allows: to evaluate and control both the separate educational modules and all educational system in general, to move right along from the assessment of separate processes and elements of the module, to module-structurally having a special purpose oriented to personality of specialist who studies in the system of postgraduate education, introduce the system of integrated assessment of the quality of educational resources and the efficiency of consumer of education services. The convenience of integral estimates is that they provide the unique numerical criterion quality.